2005
DOI: 10.1002/chem.200401053
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ammine from Platinum(II) Complexes: Implications for Cisplatin Inactivation, Storage, and Resistance

Abstract: Potential consequences of the binding of the anticancer drug cisplatin to various biomolecules in the cell have been investigated by using a combined density functional theory and continuum dielectric model approach. Since the amine ligands remain coordinated at the metal upon formation of the most frequent DNA adducts, whereas they were found to be displaced from the metal upon formation of drug metabolites, we have analyzed the factors governing amine loss from platinum(II) complexes as a possible pathway of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
77
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 76 publications
10
77
0
Order By: Relevance
“…The predominance of GSH in the cell, coupled with its conjugation abilities, means that GSH is a major player in the destructive metabolism of therapeutic compounds, acting through conjugation as a means of drug resistance 3,8,9,11 . Metal-based therapeutic compounds that are vulnerable to thiol chemistry can be structurally altered, and even deactivated, following reaction with intracellular GSH 8,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of GSH in the cell, coupled with its conjugation abilities, means that GSH is a major player in the destructive metabolism of therapeutic compounds, acting through conjugation as a means of drug resistance 3,8,9,11 . Metal-based therapeutic compounds that are vulnerable to thiol chemistry can be structurally altered, and even deactivated, following reaction with intracellular GSH 8,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Only occasionally, for example, in cases of binding of ligands with a high trans effect to cis-(NH 3 ) 2 Pt II species, has substitution of ammonia ligands been reported. [2] A while ago, we reported on another case of reactivity of NH 3 ligands, namely m-amide formation upon reaction of [Pd(en)A C H T U N G T R E N N U N G (H 2 O) 2 ] 2 + (en: ethylenediamine) with the NH 3 ligands in trans-[PtA C H T U N G T R E N N U N G (NH 3 ) 2 …”
Section: Introductionmentioning
confidence: 99%
“…A central dogma of the chemistry of the antitumor agent cis-PtCl 2 A C H T U N G T R E N N U N G (NH 3 ) 2 (cisplatin) and its amine analogues, as well as of their trans isomers, is that the am(m)ine ligands behave as inert ligands. [1] Only occasionally, for example, in cases of binding of ligands with a high trans effect to cis-(NH 3 ) 2 Pt II species, has substitution of ammonia ligands been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high potency, CDDP is only considered as an adjunct drug in pancreatic cancer treatment, usually combined with gemcitabine, because of the side effects and low efficiency caused by its fast clearance, leading to a lack of targeting and inactivation of drug during the process. 6 Recent advances in nanomaterials and nanotechnology have presented a number of promising platforms to improve the specificity and efficiency of cancer drug delivery. Lipid-or polymer-based nanoparticle delivery methods/materials and cancer-cell-targeted delivery have been studied for improving treatment by reducing side effects and enhancing drug accumulation at the tumor site using pancreatic cancer cell lines and human pancreatic tumor xenograft models.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with some previous studies that reported higher toxicity of some lipid-and polymer-formulated CDDP than free CDDP. 12,32,33 The limited amount of CDDP loaded in delivery systems (eg, less than 10 wt%), together with the inevitable deactivation of CDDP during their long-time preparation procedures (ie, long period of hydration), 6 is usually considered as one of the major reasons for reduced therapeutic efficiency. In our case, as much as 25 wt% CDDP was loaded on the CNIO-CDDP delivery system, which is significantly higher than that used in other protein drug carrier formulations.…”
mentioning
confidence: 99%